2015
DOI: 10.1007/s00394-015-1132-6
|View full text |Cite
|
Sign up to set email alerts
|

Fish consumption and frying of fish in relation to type 2 diabetes incidence: a prospective cohort study of Swedish men

Abstract: PurposeEpidemiological evidence on the association between fish consumption and risk of type 2 diabetes is heterogeneous across geographical regions. Differences related to fish consumption pattern could possibly help explain the discrepancy between the findings. We therefore aimed to investigate the association between fish consumption (total, fried, specific fish items) and type 2 diabetes incidence, taking exposure to contaminants present in fish (polychlorinated biphenyls and methyl mercury) into considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 58 publications
1
38
0
Order By: Relevance
“…The heterogeneity may also originate from differences in the type and amount of fish consumed as well as the concentrations of contaminants in fish species that were not considered in previous studies (Lee and Jacobs 2010). In fact, Wallin et al (2015) reported that dietary contaminants in fish may influence the relationship between fish consumption and T2D prevalence. Limited data on the association between fish consumption and T2D prevalence are available for the Indigenous population.…”
Section: Discussionmentioning
confidence: 96%
“…The heterogeneity may also originate from differences in the type and amount of fish consumed as well as the concentrations of contaminants in fish species that were not considered in previous studies (Lee and Jacobs 2010). In fact, Wallin et al (2015) reported that dietary contaminants in fish may influence the relationship between fish consumption and T2D prevalence. Limited data on the association between fish consumption and T2D prevalence are available for the Indigenous population.…”
Section: Discussionmentioning
confidence: 96%
“…Our results are consistent with some, but not all, previous studies assessing type 2 diabetes and fried fish intake in men and non-pregnant women. For example, in a population-based cohort of Swedish men, fried fish intake (≥6 servings/month vs. ≤1 servings/month) was significantly associated with higher risk of type 2 diabetes, (hazard ratio=1.14 ; 95% CI: 1.03, 1.31) [31]. In another study, African American women who consumed fried fish 1 to 3 times per month had 21 % higher risk of type 2 diabetes compared to women that never consumed fried fish (IRR: 1.21; 95% CI: 1.07, 1.37) [8].…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The results of studies investigating the possible associations between fish consumption and development of metabolic syndrome and type 2 diabetes mellitus (T2DM) are, however, inconsistent. [7][8][9][10][11][12] The beneficial effects of diets rich in fish have, to a large extent, been attributed to the marine n-3 PUFAs. 13,14 However, studies reporting beneficial health effects of lean fish in both animals and humans suggest that substances other than the marine n-3 PUFAs, such as fish protein, may beneficially influence metabolic health by improving insulin sensitivity, glucose metabolism, lipid status, and body composition.…”
Section: Introductionmentioning
confidence: 99%